(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
This paperanalyzes the constructs, themes and concepts that permeate the implementation of Federal Law 10.639/03. The debates presented revolve around the History of ethnic-racial relations teaching in Brazil, the setting for the creation of Law 10.639/03 and its consequences. It is a bibliographical analysis with a qualitative approach along with the theoretical perspective of decolonial, postcolonial and subaltern studies. The study allowed a critical reflection on the implementation of Law 10.639/03 and the teaching of ethnic-racial relations in Brazil. We observe that the ways of implementing the law are not linear, therefore, it is necessary to constantly analyze the different tensions, advances and limits involved in this process. Key-words: Federal Law 10.639/03. Ethnic-racial relations teaching. History teaching. Decoloniality.